2014
DOI: 10.1002/2013jc009435
|View full text |Cite
|
Sign up to set email alerts
|

Poleward ocean heat transports, sea ice processes, and Arctic sea ice variability in NorESM1-M simulations

Abstract: Results from the NorESM1-M coupled climate model were used to examine relationships between Arctic sea ice area and ocean heat transports through the primary Arctic gateways. Comparisons were made with two other models (CNRM-CM5 and MRI-CGM3) that are part of the CMIP5 archive which have the required outputs for calculating ocean heat transports. Based on an evaluation, NorESM1-M was found to be best suited to study the effects of heat transports on sea ice area, and conclusions are based on results from this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
31
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 51 publications
11
31
0
1
Order By: Relevance
“…An effect of AW heat anomalies has also been suggested for the area north of Svalbard by Onarheim et al (), and here the sea ice is observed to melt effectively if advected over warm AW in the surface layer (Peterson et al, ). The AW heat can thus reduce the sea ice cover through direct bottom melt (Sandø et al, ) and the reduction of sea ice growth during winter. The latter has been suggested to be the most important in the Barents Sea, and this is why the influence of AW is mainly a winter signal (Onarheim et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…An effect of AW heat anomalies has also been suggested for the area north of Svalbard by Onarheim et al (), and here the sea ice is observed to melt effectively if advected over warm AW in the surface layer (Peterson et al, ). The AW heat can thus reduce the sea ice cover through direct bottom melt (Sandø et al, ) and the reduction of sea ice growth during winter. The latter has been suggested to be the most important in the Barents Sea, and this is why the influence of AW is mainly a winter signal (Onarheim et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…As follows from ice melting from the bottom. The negative correlations are perhaps more surprising, though an explanation is provided by Sandø et al (2014). They find that more heat transported northward leads to less formation of sea ice in the seasonally ice-covered regions during winter.…”
Section: Discussionmentioning
confidence: 99%
“…Increased AW heat transport in recent years with both warmer water and stronger flow, was discussed by Beszczynska-Mo¨ller et al (2012), Piechura and Walczowski (2009) and Polyakov et al (2012a). Model studies of the AW heat transport and bottom melting in the Arctic Ocean suggest that periods of increased heat transport lead to enhanced bottom melting (Alexeev et al, 2013;Sandø et al, 2014). Here, we only consider AW temperature, because there is no available current meter record before the 1990s.…”
Section: Discussionmentioning
confidence: 99%